Intravenous immunoglobulin as adjunct therapy for refractory pyoderma gangrenosum: systematic review of cases and case series. (1st February 2018) - Song, H.; Lahood, N.; Mostaghimi, A.
Summary: Pyoderma gangrenosum is an uncommon skin condition in which white blood cells, neutrophils, infiltrating the skin lead to destruction and ulceration. Because early treatment is a logical approach to reducing this damage, various different treatment methods have been tried including the use of immunoglobulin, a protein extracted from blood plasma containing antibodies, given by intravenous injection (IVIG). This study is a review of previously published studies using this technique. The authors from Harvard and hospitals in Boston, U.S.A., identified 49 patients who had received this treatment after the failure of other therapies, such as oral corticosteroids and cyclosporine, to improve the condition. Most had at least one underlying disease including cancer or inflammatory bowel disease such as ulcerative colitis. The skin damage affected different body sites such as the lower limbs or trunk. In most cases the patients were also receiving oral corticosteroids at the time of the IVIG treatment. Over half the patients responded completely to the treatment with IVIG in addition to steroids, with a substantial number of the remainder responding in part to this therapy. The most common side effect was nausea or headache although rashes and fever were also seen. Overall these results suggest that it is a potentially useful therapy for patients who have not responded to other medications used to treat this condition.